The nickel ride ; & 99 and 44/100% dead! [videorecording (DVD)] - Grusin, Dave; Mancini, Henry (Distributed by Shout! Factory LLC, 2011)
The nickel ride: "Cooper ... known as the "key man" because of his large ring of keys, manages several warehouses containin the Mob's stolen goods. When the Mob has stolen so much that they are running out of space, they send Cooper to negotiate for a new warehouse. His boss gets nervous and, believing the big-hearted "key man" to be more of a risk than an asset, orders him to be watched"--Container